Both quantity and quality of antenatal care matter for child birthweight: An analysis of nationally representative data From Bangladesh, India, Nepal, and Pakistan - Neupane, Sumanta; Scott, Samuel P.; Nguyen, Phuong Hong; Menon, Purnima (American Society for Nutrition, 2021)
Antenatal care (ANC) is an important platform to deliver health and nutrition interventions during pregnancy but there is limited evidence on how both the number and content of ANC visits relate to birth outcomes. We examined the independent and additive contributions of ANC quantity and quality on child birthweight in four South Asian countries.